A comparative study of branched and linear mannitol-based amphiphiles on membrane protein stability. Issue 23 (18th October 2018) - Hussain, Hazrat; Helton, Tyler; Du, Yang; Mortensen, Jonas S.; Hariharan, Parameswaran; Ehsan, Muhammad; Byrne, Bernadette; Loland, Claus J.; Kobilka, Brian K.; Guan, Lan; Chae, Pil Seok
Abstract : The comparative study on linear vs . branched alkyl-chain amphiphiles indicates a favorable role for branched alkyl-chains in stabilizing membrane proteins. Abstract : The study of membrane proteins is extremely challenging, mainly because of the incompatibility of the hydrophobic surfaces of membrane proteins with an aqueous medium. Detergents are essential agents used to maintain membrane protein stability in non-native environments. However, conventional detergents fail to stabilize the native structures of many membrane proteins. Development of new amphipathic agents with enhanced efficacy for membrane protein stabilization is necessary to address this important problem. We have designed and synthesized linear and branched mannitol-based amphiphiles (MNAs), and comparative studies showed that most of the branched MNAs had advantages over the linear agents in terms of membrane protein stability. In addition, a couple of the new MNAs displayed favorable behaviors compared to n -dodecyl-β-d -maltoside and the previously developed MNAs in maintaining the native protein structures, indicating potential utility of these new agents in membrane protein study.